2020
DOI: 10.15587/2519-4852.2020.197270
|View full text |Cite
|
Sign up to set email alerts
|

Technological aspects of obtaining liquid extracts of black poplar buds and determining the strategy for their standardization at the pharmaceutical development stage

Abstract: Проведення досліджень з розробки технології одержання рідких екстрактів тополі чорної бруньок, їх стандартизації та визначення оптимальних параметрів технологічного процесу екстракції, які мають забезпечити необхідний вміст біологічно активних речовин та фармакологічну активність препарату. Методи. Виготовлення рідких екстрактів проводили методом перколяції. Кількісне визначення суми похідних гідроксикоричної кислоти здійснювали за уніфікованою спектрофотометричною методикою, рекомендованою Державною фармакопе… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Results showed that the concentration of the extracting and infusion time influence the qualitative composition of the extract. For obtaining an extract rich in hydroxycinnamic acids (57.70%), it is advisable to use ethanol (70%) and for flavonoids (82.60%), it is advisable to use ethanol (96%) [28].…”
Section: Phytochemical Composition Of Populus Nigra L Budsmentioning
confidence: 99%
“…Results showed that the concentration of the extracting and infusion time influence the qualitative composition of the extract. For obtaining an extract rich in hydroxycinnamic acids (57.70%), it is advisable to use ethanol (70%) and for flavonoids (82.60%), it is advisable to use ethanol (96%) [28].…”
Section: Phytochemical Composition Of Populus Nigra L Budsmentioning
confidence: 99%